High-Efficient Nd：YLF Q-Switched Laser Operating at 523.5 nm - 陆婷婷 马剑 黄敏捷 杨琦 朱小磊 陈卫标 (Chinese physics letters, 2014)
An intracavity frequency doubling electro-optically Q-switched Nd： YLF 523.5 nm laser is developed. An appropriate cylindrical lens is employed in the oscillator to optimize the mode size and to improve the stability of the cavity. With an incident pump pulse energy of 58 mJ at a 500 Hz repetition rate, a green pulse energy of 16.8 mJ at 523.5 nm is obtained, corresponding to an optical-optical conversion efficiency of 29%. The pulse width is less than 8 ns, and the beam quality factor is M^2≤ 2.5.